Recent trends in social and behaviour sciences : proceedings of the 2nd International Congress on Interdisciplinary Behavior and Social Sciences 2013 (ICIBSoS 2013), Jakarta, Indonesia, 4-5 November 2013 /: proceedings of the 2nd International Congress on Interdisciplinary Behavior and Social Sciences 2013 (ICIBSoS 2013), Jakarta, Indonesia, 4-5 November 2013. ([2014]) - Unknown
No abstract available